1999
DOI: 10.1046/j.1365-2141.1999.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the p53 gene in juvenile myelomonocytic leukaemia

Abstract: Juvenile chronic myelomonocytic leukaemia (JMML) is a rare myeloproliferative disorder of childhood. Fewer than 30% of cases of JMML terminate in a blast crisis; however, its molecular mechanism is unknown. Since mutation and/or deletion of the p53 gene has been reported to be associated with disease progression in a wide variety of human cancers, including adult‐type chronic myelogenous leukaemia, we studied the p53 gene in 20 patients with JMML (16 samples in chronic phase and seven at blast crisis). Exons 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 47 publications
0
45
0
1
Order By: Relevance
“…[22][23][24][25][26][27][28] Here we report a RAS mutation frequency of approximately 14% in a large (n>100) cohort of infant ALL cases, and a frequency of approximately 24% in infant ALL patients carrying MLL translocation t(4;11). These results are not consistent with previously published studies that reported either high RAS mutation frequency of 50%, or a total absence of RAS mutations in MLL-rearranged ALL.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Here we report a RAS mutation frequency of approximately 14% in a large (n>100) cohort of infant ALL cases, and a frequency of approximately 24% in infant ALL patients carrying MLL translocation t(4;11). These results are not consistent with previously published studies that reported either high RAS mutation frequency of 50%, or a total absence of RAS mutations in MLL-rearranged ALL.…”
Section: Discussionmentioning
confidence: 99%
“…NF1 wild type allele is frequently deleted and the Ras genes never mutated in children with neuro®bromatosis. In contrast, Ras mutations exist in patients with myeloid tumors that do not have neuro®bromatosis Neubauer et al, 1991;Miyauchi et al, 1994). A mutual exclusion e ect may indicate that both mutations are able, on their own, of fully activating the Ras proliferative pathway and, therefore, an additional mutation would not provide increased proliferative capacity.…”
Section: Mechanism Of Nf1 Tumor Suppressionmentioning
confidence: 99%
“…35% of JMML patients have mutations in SHP2 (12)(13)(14), a protein-tyrosine phosphatase that positively regulates the RAS signaling pathway (15,16). RAS-activating mutations account for another 20 -25% of JMML-associated mutations (17)(18)(19). Several groups determined that a proportion of JMML patients have 11q uniparental disomy.…”
Section: Juvenile Myelomonocytic Leukemia (Jmml) Is Characterized By mentioning
confidence: 99%